2009
DOI: 10.1523/jneurosci.4212-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol Targets Mitochondria to Regulate Intracellular Ca2+Levels

Abstract: Cannabinoids and the endocannabinoid system have attracted considerable interest for therapeutic applications. Nevertheless, the mechanism of action of one of the main nonpsychoactive phytocannabinoids, cannabidiol (CBD), remains elusive despite potentially beneficial properties as an anti-convulsant and neuroprotectant. Here, we characterize the mechanisms by which CBD regulates Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
170
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(196 citation statements)
references
References 67 publications
9
170
1
4
Order By: Relevance
“…In the present study, administration of KA to rats to induce epilepsy caused persistent activation of glutamate AMPA/kainate receptors triggering a sustained neuronal influx of Na + and Ca 2+ , causing prolonged depolarization and prolonged Ca 2+ influx into the cytoplasm. However, previous studies suggest that CBD exerts an activity‐dependent biphasic control over Ca 2+ levels (Ryan et al, 2009); hence, it is likely that in our experiments, CBD treatment of epileptic rats exerted a neuroprotective function by preventing intracellular Ca 2+ overloading during hyperactivity, thus halting oxidative stress. This would trigger mitochondrial oxidation (Hajnoczky et al, 2006), contributing to the degenerative process of neurons (Liang et al, 2000; Patel, 2004; Waldbaum et al, 2010).…”
Section: Discussionmentioning
confidence: 71%
“…In the present study, administration of KA to rats to induce epilepsy caused persistent activation of glutamate AMPA/kainate receptors triggering a sustained neuronal influx of Na + and Ca 2+ , causing prolonged depolarization and prolonged Ca 2+ influx into the cytoplasm. However, previous studies suggest that CBD exerts an activity‐dependent biphasic control over Ca 2+ levels (Ryan et al, 2009); hence, it is likely that in our experiments, CBD treatment of epileptic rats exerted a neuroprotective function by preventing intracellular Ca 2+ overloading during hyperactivity, thus halting oxidative stress. This would trigger mitochondrial oxidation (Hajnoczky et al, 2006), contributing to the degenerative process of neurons (Liang et al, 2000; Patel, 2004; Waldbaum et al, 2010).…”
Section: Discussionmentioning
confidence: 71%
“…Under normal physiological Ca 2+ conditions, CBD slightly increases intracellular Ca 2+ , whereas CBD reduces intracellular Ca 2+ under high-excitability conditions. These changes were blocked by the pretreatment with an antagonist of the mitochondrial Na + / Ca 2+ exchanger, suggesting a mitochondrial site of action [111]. CBD also produces biphasic changes in intracellular calcium levels via antagonism of the mitochondrial voltagedependent anion channel 1 [112].…”
Section: Cbdmentioning
confidence: 98%
“…CBD exerts dynamic control over intracellular calcium stores through multiple, activity-dependent pathways [110,111]. CBD induces a bidirectional change in intracellular calcium levels that depends on cellular excitability.…”
Section: Cbdmentioning
confidence: 99%
“…VDAC1 plays a key role in controlling calcium flux into mitochondria, and intracellular calcium can increase VDAC1 expression and oligomerization, which is associated with increased apoptosis; in particular, it is thought that VDAC1 selectively transfers apoptotic calcium signals to the mitochondrion [226,227]. Two other groups have also shown that CBD could apparently control intracellular calcium flux in a mitochondrially dependent way, which, overall, suggests that CBD, via a VDAC1-related mechanism, could play an important role in controlling calcium flux in neurodegeneration [228,229].…”
Section: Cbd Ion Channels Targets In Neurodegenerationmentioning
confidence: 99%